2004
DOI: 10.1038/sj.leu.2403390
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid inhibits proliferation and induces apoptosis in acute myeloid leukemia cells expressing P-gp and MRP1

Abstract: The multidrug resistance (MDR) phenotype, induced by the overexpression of several ABC transporters or by antiapoptotic mechanisms, has been identified as the major cause of drug resistance in the treatment of patients with acute myeloid leukemia (AML). In this study, we have shown that valproic acid (VPA) (a histone deacetylase inhibitor) can inhibit the proliferation of both P-glycoprotein (P-gp)-and MDR-associated protein 1 (MRP1)-positive and -negative cells. VPA also induced apoptosis of P-gp-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 23 publications
3
84
0
Order By: Relevance
“…However, VPA had weaker effects than lithium. We supposed that SK-N-SH is a neuroblastoma cell, and it is known that VPA can induce apoptosis in several tumor cells (55)(56)(57). Additionally, we observed that Htt590-100Q (K444R) was more likely to localized in the nucleus when compared with Htt590-100Q in the SK-N-SH cells; however, there was no difference in the HeLa cells.…”
Section: Lithium-induced Down-regulation Of Hdac1 Is Essential For Thmentioning
confidence: 40%
“…However, VPA had weaker effects than lithium. We supposed that SK-N-SH is a neuroblastoma cell, and it is known that VPA can induce apoptosis in several tumor cells (55)(56)(57). Additionally, we observed that Htt590-100Q (K444R) was more likely to localized in the nucleus when compared with Htt590-100Q in the SK-N-SH cells; however, there was no difference in the HeLa cells.…”
Section: Lithium-induced Down-regulation Of Hdac1 Is Essential For Thmentioning
confidence: 40%
“…We and others have reported that chemical and genetic inhibition of HDACs leads to decreased expression of FLIP mRNA (36)(37)(38)(39)(40)(41)(42)(43). However, the mechanism by which inhibiting HDACs decreases FLIP expression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity assays were conducted with HL-60, a VPA-sensitive cell line, and varying VPA concentrations alone or in combination with a minimally cytotoxic gemcitabine concentration (10 nmol/L; ref. 33). VPA was cytotoxic at concentrations of 1 mmol/L and potentiated gemcitabine activity when present at 1,000-fold higher concentration (0.1 mmol/L; data not shown).…”
Section: Valproic Acidmentioning
confidence: 99%